2013
DOI: 10.1016/j.bbamem.2012.09.021
|View full text |Cite
|
Sign up to set email alerts
|

A novel antimicrobial peptide derived from modified N-terminal domain of bovine lactoferrin: Design, synthesis, activity against multidrug-resistant bacteria and Candida

Abstract: Lactoferrin (LF) is believed to contribute to the host's defense against microbial infections. This work focuses on the antibacterial and antifungal activities of a designed peptide, L10 (WFRKQLKW) by modifying the first eight N-terminal residues of bovine LF by selective homologous substitution of amino acids on the basis of hydrophobicity, L10 has shown potent antibacterial and antifungal properties against clinically isolated extended spectrum beta lactamases (ESBL), producing gram-negative bacteria as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 48 publications
1
38
0
Order By: Relevance
“…Many studies have shown that the biological properties of LF are closely associated with the N-lobe (Mishra et al, 2013). In this study, the N-terminal of porcine lactoferrin gene was expressed using a Lactobacillus secretion expression vector and the resulting recombinant protein exhibited antibacterial activity against Escherichia coli, Salmonella enterica ssp.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that the biological properties of LF are closely associated with the N-lobe (Mishra et al, 2013). In this study, the N-terminal of porcine lactoferrin gene was expressed using a Lactobacillus secretion expression vector and the resulting recombinant protein exhibited antibacterial activity against Escherichia coli, Salmonella enterica ssp.…”
Section: Discussionmentioning
confidence: 99%
“…The samples were processed according to the method described by Mishra et al [14]. The sections were observed under a Morgagni-268 electron microscope under standard operating conditions.…”
Section: Transmission Electron Microscopymentioning
confidence: 99%
“…L10 was further tested against 30 multidrug-resistant isolates of extended spectrum β-lactamase (ESBLs) producing bacteria, including P. aeruginosa, K. pneumoniae and Acinobacter species with the MICs reported to be in the range of 1-8 µg/ml, while also having an MIC of 6.25 µg/ml against C. albicans. In addition L10 showed no hemolytic activity, even at high concentrations of 800 µg/ml [126].…”
Section: Small Peptide Librariesmentioning
confidence: 99%